Perencanaan Karir Karyawan di PT X - Marta Dina Narulita (Jurnal Wacana Ekonomi, 2019)
An establishment has a lot of resources, and human resources is one of the resources. Human resource is the most crucial asset for the company, because human resource is the one which determines the success of the company. This research is intended to find out the implementation of carrier planning at PT. X. The method used in this research is descriptive. Techniques of data collecting used are bibliography study, interviewing, and distributing questionnaires. While for reprocessing the questionnaire, researchers used Likert Scale. The sampling technique used is census sampling technique, out of 20 employees of The Human Resource Department at PT. X. The result of research shows that the implementation of carrier planning at PT. X is generally good. Organization appraisal about the ability and capability of the employee is in good criteria, but in individual performance appraisal about interest of employees, career needs, and career goals, the organization role in giving the career information to the employees, and the organization role in giving the career counselling to the employees are in bad criteria. The four mentioned things show that the implementation of career planning has not been optimum.